THEORETICAL PERSPECTIVES ON LANGUAGE ACQUISITION IN CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL): BRIDGING CONTENT AND COMMUNICATION - George, Arun; Jacob, Jalson (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The convergence happening in Content and Language Integrated Learning (CLIL) and the resultant acquisition of a language (L2) involves integration of several Second Language Acquisition (SLA) and subject learning theories. The SLA theories support this method of learning where L2 acquisition happens when subject is learned through interaction. This paper points out some of the theoretical underpinnings behind a successful and practical L2 acquisition happening in CLIL.